Angiopoietin-2 and the Vascular Endothelial Growth Factor Promote Migration and Invasion in Hepatocellular Carcinoma- and Intrahepatic Cholangiocarcinoma-Derived Spheroids - Adriana Romanzi; Fabiola Milosa; Gemma Marcelli; Rosina Maria Critelli; Simone Lasagni; Isabella Gigante; Francesco Dituri; Filippo Schepis; Massimiliano Cadamuro; Gianluigi Giannelli; Luca Fabris; Erica Villa (Biomedicines, 2023)
Aggressive hepatocellular carcinoma (HCC) overexpressing Angiopoietin-2 (ANG-2) (a protein linked with angiogenesis, proliferation, and epithelial–mesenchymal transition (EMT)), shares 95% of up-regulated genes and a similar poor prognosis with the proliferative subgroup of intrahepatic cholangiocarcinoma (iCCA). We analyzed the pro-invasive effect of ANG-2 and its regulator vascular endothelial growth factor (VEGF) on HCC and CCA spheroids to uncover posUsible common ways of response. Four cell lines were used: Hep3B and HepG2 (HCC), HuCC-T1 (iCCA), and EGI-1 (extrahepatic CCA). We treated the spheroids with recombinant human (rh) ANG-2 and/or VEGF and then observed the changes at the baseline, after 24 h, and again after 48 h. Proangiogenic stimuli increased migration and invasion capability in HCC- and iCCA-derived spheroids and were associated with a modification in EMT phenotypic markers (a decrease in E-cadherin and an increase in N-cadherin and Vimentin), especially at the migration front. Inhibitors targeting ANG-2 (Trebananib) and the VEGF (Bevacizumab) effectively blocked the migration ability of spheroids that had been stimulated with rh-ANG-2 and rh-VEGF. Overall, our findings highlight the critical role played by ANG-2 and the VEGF in enhancing the ability of HCC- and iCCA-derived spheroids to migrate and invade, which are key processes in cancer progression.